110 Specialist Palliative Care Paramedics. (14th March 2023) - Davies, Gwenllian; O'Brian, Ed; Williams, Anthony; Davies-Kumar, Sian; Hewes, Beth; Ashford, Rosanna; Lilley, Rachel; Chohan, Andedep
Abstract : Background: Globally, community healthcare teams struggle to meet the growing demand for effective and responsive palliative care enabling patients to remain at home when appropriate. With this in mind, Swansea Bay University Health Board (SBUHB) have implemented an innovative service development, in which paramedics with enhanced training and support, help achieve this. Methods: Six paramedics were given tailored training in advanced communication skills, end-of-life assessment and symptom management. A review of the triage, circumstances and outcomes of all 157 paramedic visits during one month was conducted to determine unmet need, effectiveness of the paramedic model, its congruity with ongoing community nursing models and its impact upon primary and secondary care workload. Results: Most calls came from relatives of patients already known to the Specialist Palliative Care Team (SPCT). 80% of visits were carried out due to a sudden deterioration in condition or urgent symptom control need. 16% required either prescription and/or administration of 'just in case' medication. Over 50% of GP visits and 22% of secondary care admissions were avoided. Conclusions: Coupled with exceptional feedback from recipients and care providers alike, this review demonstrates palliative paramedics' ability to provide expeditious face to face assessments, symptom management and vital reassurance, as well as to triangulate care between primary and secondary care providers. Issues in relation to procuring and administering prescribed items could prompt new prescribing regulations for Palliative Paramedics. Further review should help streamline this model and could see its expansion in SBUHB and its adoption by other health boards.